A164: Development of Pediatric Item Banks to Measure Pain Behavior in the Patient Reported Outcomes Measurement Information System. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - DeWitt, Esi Morgan; Barnett, Kimberly; Farrell, Jennifer; Revicki, Dennis; Carle, Adam; Cook, Karon; Goldschneider, Kenneth; Dampier, Carlton; Sherry, David D.; Kashikar‐Zuck, Susmita; Chen, Wen‐Hung
Abstract : Background/Purpose: The NIH Patient Reported Outcomes Measurement Information System (PROMIS) has created publicly available patient reported outcomes measures in several domains of physical, social and emotional health. Measurement of pediatric pain in PROMIS is currently limited to pain interference. Pain behaviors are observable actions orreactions that communicate pain including verbal, nonverbal and pain reducing behaviors. Numerous validated parent/provider‐rating scales of pain behavior in children exist but there are currently no validated self‐report measures of pain behavior in school‐age children and adolescents. Such measures could be useful in establishing targets for treatment and assessing outcomes. The aim of this study is to enhance PROMIS pediatric pain assessment by developing and testing pediatric pain behavior item banks for self‐ and proxy‐report. Methods: Candidate items were developed through a qualitative item review process, and were in the format, "In the past 7 days, when I was in pain …" Patients ages 8 to 17 years, or parents/guardians of children, with a chronic painful condition (fibromyalgia, juvenile idiopathic arthritis, sickle cell disease) were recruited through outpatient clinics at 3 centers. Child participants completed approximately 100 PROMIS items concerning their pain (including 47 candidate pain behavior items), physical function, fatigue, and psychosocial well/being. Proxies responded to sociodemographic and health history items and 51 new candidate proxy‐report pain behavior items were collected. A confirmatory factor analysis (CFA) was performed on the child and guardian pain behavior data, with model fit assessed by the comparative fit index (CFI) and root mean square error of approximation (RMSEA). Item response theory (IRT) analysis was performed on the pain behavior items based on the graded response model. Differential item functioning (DIF) was assessed by age group and disease group. Results: 450 children (71% female, Mage 13.54), and 232 proxies participated. CFA indicated unidimensionality in the child (CFI = 0.962; RMSEA = 0.079) and proxy pain behavior responses (CFI = 0.970; RMSEA = 0.080). The responses for the child and proxy data had good IRT model fit and were free of local dependence. Slopes for the pediatric responses ranged from 1.81 ("rubbed body where hurt") to 4.40 ("moved slower"), and thresholds ranged from −2.00 to 4.95. For the proxy data, slopes ranged from 1.51 ("think of something fun") to 3.48 ("tried not to move"), and thresholds ranged from −3.02 to 2.43. Items performed well across disease groups and age. There was little DIF either by age group (8–12, 13–18) or by sample (child vs. proxy). Child and proxy scores were correlated at 0.70. Correlations between pain behavior and pain intensity were 0.60 in children and 0.65 in proxy sample. Conclusion: The PROMIS pediatric pain behavior item‐banks for self and proxy report are suitable for use in non‐adaptive format as short forms or in dynamic format as computerized adaptive tests in clinical research with the potential for adoption into clinical care.